KEANEKARAGAMAN PLANKTON DI DANAU SIMBAD DESA PULAU BIRANDANG KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR PROVINSI RIAU - Dedi Hidayat; Roza Elvyra; Fitmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
ewline"> Simbad lake was formed naturally from the input of Kampar river overflowing water during flood season and its tributaries. Simbad lake have been affected by various people activities eg. plantation. This research was aimed to study the diversity of plankton and also its relation with water physical–chemical factors in Simbad Lake. Sampling was conducted at date of 16 February and 16 March 2014 using purposive method considering environmental condition. The result showed that the composition of plankton during sampling in February consisted of 47 genera which were divided into 26 genera of phytoplankton and 21 genera of zooplankton. Meanwhile, during sampling in March it consisted of 35 genera which were divided into 21 genera of phytoplankton and 14 genera of zooplankton. The abundance of plankton from February to March within phytoplankton was dominated by Bacillariophyceae, while zooplankton was dominated by Branchiopoda. The diversity index for phytoplankton and zooplankton sampled in February were range from 0,16-1,21 and 0,01-0,15, respectively. Furthermore, the diversity index for phytoplankton and zooplankton sampled in March ranging from 0,9–1,25 and 0,02–0,12. Physical – chemical factors of water that most affect the diversity value of plankton in Simbad Lake is the current speed.